Homotropic Allosteric Regulation in Monomeric Mammalian Glucokinase - Larion, Mioara (2011)
Glucokinase catalyzes the ATP-dependent phosphorylation of glucose, a chemical transformation that represents the rate-limiting step of glycolytic metabolism in the liver and pancreas. Glucokinase is a central regulator of glucose homeostasis as evidenced by its association with two disease states, maturity onset diabetes of the young (MODY) and persistent hyperinsulinemia of infancy (PHHI). Mammalian glucokinase is subject to homotropic allosteric regulation by glucose — the steady-state velocity of glucose 6-phosphate production is not hyperbolic, but instead displays a sigmoidal response to increasing glucose concentrations. The positive cooperativity displayed by glucokinase is intriguing since the enzyme functions as a monomer under physiological conditions and contains only a single binding site for glucose. Despite the existence of several models of kinetic cooperativity in monomeric enzymes, a consensus has yet to be reached regarding the mechanism of allosteric regulation in glucokinase. Experimental evidence collected over the last 45 years by a number of investigators supports a link between cooperativity and slow conformational reorganizations of the glucokinase scaffold. In this review, we summarize advances in our understanding of glucokinase allosteric regulation resulting from recent X-ray crystallographic, pre-equilibrium kinetic and high-resolution nuclear magnetic resonance investigations. We conclude with a brief discussion of unanswered questions regarding the mechanistic basis of kinetic cooperativity in mammalian glucokinase.